A systematic literature review of carbon footprint decision-making approaches for infrastructure and building projects. (1st April 2023) - Fang, Zigeng; Yan, Jiayi; Lu, Qiuchen; Chen, Long; Yang, Pu; Tang, Junqing; Jiang, Feng; Broyd, Tim; Hong, Jingke
Highlights: 31 out of 1465 studies were selected for different CF decision-making stages; The paper assessed five key CF decision-making stages for both building and infrastructure; A generalised CF management decision-making framework was developed. Abstract: There is an urgent need for all industries to go beyond the existing set of policies against greenhouse gas (GHG) emissions to combat climate change. As the major producer (19%) of GHG, the construction industry needs to optimise its carbon footprint (CF) decision-making processes to provide better management solutions against global warming. Identification and evaluation of the key factors that affect CF decision-making are critical yet limited. Based on our knowledge, no existing study compares the different characteristics of construction projects' CF management approaches through the whole life cycle phases (including assessment, optimisation, and comparison) to enable CF-related knowledge transfer between the building and infrastructure sectors. To meet these knowledge gaps, this paper reviewed 1, 465 studies related to infrastructure and building CF projects and selected 31 studies to evaluate academic researchers' contributions toward the different CF decision-making stages for the building and infrastructure projects' whole lifecycle. The paper systematically reviewed and assessed the existing information in five key CF decision-making stages: project drafting stage, methodology choosing stage, data collection stage, CF analysis stage, and CF visualisation stage. A generalised CF decision-making framework is also developed to inform future CF management. The limitations of the existing studies and the benefits of the developed framework were summarised. This study identifies the key information required from the perspective of CF management decision-makers and contributes a universal CF decision-making framework for state-of-the-art CF management practice.